Indoor Positioning System Infrastructure Based on Triangulation Method through Visible Light Communication - Apnan Juanda; Willy Anugrah Cahyadi; Angga Rusdinar; Denny Darlis (Ultima Computing : Jurnal Sistem Komputer, 2022)
Autonomous mobile robots are widely used in industry to help human’s work, but the concept has a weakness, that is robot still does not know its position in a room so it can not detect whether the robot has been at destination point. The technology commonly used to determine the position of objects is the Global Positioning System (GPS). However, GPS does not detect objects that are indoors. Previous research used Wi-Fi as a reference for designing an indoor positioning system, but the system could not determine the position in detail because Wi-Fi could only detect object zones. Based on these problems, this research will propose the infrastructure prototype design of an indoor positioning system based on Visible Light Communication (VLC). The main focus of this research is designing a VLC transmitter and receiver system, estimating the distance between the receiver and transmitter based on the received signal strength, and estimating the receiver's position using the triangulation method based on a minimum of 3 distance estimates. The estimating distance system get average accuracy is 76.47%. The estimated accuracy of the x-coordinate position has the best accuracy is 77.05% and the y-coordinate estimate has the best accuracy is 86.54%.